Dances with Spiders : Crisis, Celebrity, and Celebration in a Southern Italy. - Lüdtke, Karen (Epistemologies of Healing, 2., 2008)
For centuries, the rite of the tarantula was the only cure for those 'bitten' or 'possessed' by the mythic Apulian spider. Its victims had to dance to the local tarantella or 'pizzica' for days on end. Today, the pizzica has returned to the limelight, bringing to the forefront issues of performance, gender, identity and well-being. This book explores how and why the pizzica has boomed in the Salento and elsewhere and asks whether this current popu- larity has anything to do with the historic ritual of tarantism or with the intention of recovering well-being. While personal stories and experien.